ANALISIS KONSUMSI ENERGI LISTRIK UNTUK PENCAPAIAN EFISIENSI ENERGI DI KANTOR DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TOJO UNA-UNA - Duldes S. Lambey; Nurhani Amin; Yulius S. Pirade; Rudi Santoso (Foristek, 2021)
Audit of Electrical Energy at the Regional House of Representatives of the Tojo Una-Una District is a comprehensive method in examining energy use in a building to find the value of Energy Consumption Intensity (IKE) and Energy Saving Opportunities (PHE) that can be obtained to reduce energy waste so that the consumption of electrical energy is more effective and efficient. The audit of Electrical Energy is carried out according to SNI 03-6196-2000 concerning Energy audit procedures in buildings and the Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 13 of 2012 concerning Savings Electricity Consumption. The results of the evaluation of the Energy Consumption Intensity Calculation conducted at the Office of the Regional House of Representatives of Tojo Una-Una District known that there are 16 rooms with the criteria for the Energy Consumption Intensity (IKE) value, namely an office building with air conditioning has efficient enough 8 rooms, wasteful 3 rooms and based on office buildings without Air-conditioning is quite efficient in 3 rooms and wasteful in 2 rooms. The results of Energy Saving Opportunities (PHE) that have been identified by using air conditioning and energy-saving lamps, reducing hours of use without reducing the quality of service in the office can save electricity consumption of 2.339,5165 kWh/month or save electricity bill payments of IDR. 3.379.899,60/month.